Implementation of a finite element analysis procedure for structural analysis of shape memory behaviour of fibre reinforced shape memory polymer composites. (30th October 2017) - Azzawi, Wessam Al; Epaarachchi, J A; Islam, Mainul; Leng, Jinsong
Abstract: Shape memory polymers (SMPs) offer a unique ability to undergo a substantial shape deformation and subsequently recover the original shape when exposed to a particular external stimulus. Comparatively low mechanical properties being the major drawback for extended use of SMPs in engineering applications. However the inclusion of reinforcing fibres in to SMPs improves mechanical properties significantly while retaining intrinsic shape memory effects. The implementation of shape memory polymer composites (SMPCs) in any engineering application is a unique task which requires profound materials and design optimization. However currently available analytical tools have critical limitations to undertake accurate analysis/simulations of SMPC structures and slower derestrict transformation of breakthrough research outcomes to real-life applications. Many finite element (FE) models have been presented. But majority of them require a complicated user-subroutines to integrate with standard FE software packages. Furthermore, those subroutines are problem specific and difficult to use for a wider range of SMPC materials and related structures. This paper presents a FE simulation technique to model the thermomechanical behaviour of the SMPCs using commercial FE software ABAQUS. Proposed technique incorporates material time-dependent viscoelastic behaviour. The ability of the proposed technique to predict the shape fixity and shape recovery was evaluated by experimental data acquired by a bending of a SMPC cantilever beam. The excellent correlation between the experimental and FE simulation results has confirmed the robustness of the proposed technique.